Investigasi Penerimaan dari Aplikasi E-Learning Menggunakan Technology Acceptance Model (TAM) 3 Case Report : e-learning STMIK Rosma - Setiyani, Lila; Suhada, Karya; Effendy, Femmy (Research Center and Case Clearing House PPM School of Management, 2021)
This study aims to measure the level of e-learning adoption from a tertiary institution that has applied e-learning during the COVID-19 period. The TAM 3 model was chosen to measure the level of e-learning adoption. This study involved 100 respondents from students of the 2020 STMIK ROSMA class. The results of data collection were analyzed using the Structural Equation Model (SEM) with the help of SmartPLS 3 software. The results of this research hypothesis test indicate that image has a positive effect on the perceived usefulness of e-learning, anxiety of e-learning users is not proven to have a positive effect on perceived ease of use e-learning, self-confidence is proven to have a positive influence on the perceived ease of e-learning users, conditions that facilitate e-learning users are not proven to have a positive effect on the perceived ease of e-learning users, the quality of results has a positive influence on the perceived usefulness of e-learning, intention to use e-learning has a positive influence on the adoption of e-learning, subjective norms have a positive effect on e-learning images, subjective norms have a positive effect on intention to use e-learning, subjective norms are not proven to have a positive effect on intention to use e-learning, the perceived usefulness of e-learning has a positive influence on the intention of using e-learning, the perceived ease of e-learning users has a positive influence on the intention to use e-learning, the perception of the ease of using e-learning has a positive influence on the perceptions of e-learning users, the perception pleasure has a positive influence on the perceptions of e-learning users. The results of this study can be an evaluation for STMIK ROSMA in implementing e-learning